On Some Topical Problems of the General Theory of Legal Consciousness - Kozhevnikov, Vladimir Valentinovich (Budapest International Research and Critics University, 2020)
This scientific article examines problematic issues about the subject of reflection of legal consciousness and its structure. The purpose of this study was those problems of legal consciousness that relate to the subject of its reflection and structure. The implementation of this goal involves the solution of the following tasks: 1) analysis of the subject of reflection of legal consciousness; 2) analysis of the structure of legal consciousness. As a result of the study, the author came to the following conclusions: 1) legal consciousness as a set of ideas and feelings expresses its attitude not only to the current and desirable law, but also to the law of the past; 2) taking into account the close connection between the state and law, their interaction in various forms, the subject of reflection of legal consciousness should be defined through the category